Ecological impact and population status of non-native bees in a Brazilian urban environment - Graf,Letícia Vanessa (2020)
Abstract The introduction of species is an important global threat to native ecosystems and yet little is known about invasion risks of non-native bees. Moreover, urbanization is increasing rapidly around the world with impact on the bee fauna. The city of Curitiba (Brazil) could be considered a model system for studies under this scope, with historical samplings and monitoring programs since the 1940s. This paper aims to quantify the current ecological impact of the non-native bee species present in Curitiba by using an integrative measure of impact and to define their current population status by classifying them into a unified framework for biological invasions. Ten sites were actively sampled in the metropolitan area of Curitiba during ten months. In addition to Apis mellifera Linnaeus, 1758, we found two others non-native species, Anthidium manicatum (Linnaeus, 1758) and Melipona scutellaris Latreille, 1811. None of them changed the native bee community structure, but they got different values of impact due to their ranges and abundances. While the honeybee is a known invasive species, A. manicatum was also considered invasive and has persisted in the city since the 1940s, interacting with the non-native plant Leonurus japonicus Houtt. M. scutellaris, a cultivated stingless bee species, had its first record for the city and fits the casual non-native category. We suggest monitoring the non-native bee species and actions centered on beekeepers to avoid future illegal introductions. The honey production or hobby interest on stingless bees can offer additional obstacles for species conservation when decoupled of scientific knowledge.